The orchid flora of Barra Honda National Park, Nicoya, Guanacaste, Costa Rica - Bogarín Chaves, Diego Gerardo (2021)
Barra Honda National Park (BHNP) lies in the Tempisque River Basin of the Península de Nicoya, Guanacaste, Costa Rica. The Park is well known for its limestone caverns, which date from the Upper Paleocene–Lower Eocene and are the main attraction of BHNP. The area shows a marked climatic seasonality with a predominantly semideciduous tropical dry forest. We present a floristic treatment of the orchids of BHNP based on field collections, herbarium sampling, and documentation of living specimens. We discuss the biodiversity, climate, geology, and topography of the Park and provide a novel vegetation zones map with eight floristic associations: bean plantations, disturbed secondary forest, evergreen forest, jaragua fields, mature secondary forests, pastures, rocky areas, karstic limestone pavement, and young secondary forest. For the 36 species belonging to 29 genera recorded, we provide composite line drawings and Lankester composite digital plates, descriptions, distribution, ecology, etymology, synonymy, taxonomy, photographs, and a key to the species for field identification based on morphology. Ten species of orchids (27.8%) are terrestrials and 26 are epiphytes (72.2%). The evergreen forest contains 80% of the orchid species of BHNP. We describe Pelexia barrahondaensis and Sarcoglottis calcicola as new to science, and we propose a new combination under Specklinia for Pleurothallis panamensis. Also, we record the terrestrial orchid genus Tropidia for the first time in Costa Rica. The present study provides new information on the Nicoya Peninsula’s dry forest ecosystems for in situ conservation and research. This work can be useful for other protected areas within the same ecosystem that lack a floristic treatment of the Orchidaceae.